Dairy effluent treatment and lipids production by Chlorella pyrenoidosa and Euglena gracilis: study on open and closed systems. Issue 3 (28th March 2014) - Yadavalli, Rajasri; Rao, C. S.; Rao, Ramgopal S.; Potumarthi, Ravichandra
ABSTRACT Organic content and nutrients from dairy effluent by immobilized Chlorella pyrenoidosa and Euglena gracilis were removed in both open and closed systems. Biochemical constituents viz, carbohydrates, lipids, and proteins were analyzed to assess the changes in their proximate composition in both the systems for both species. Euglena gracilis has a high lipid content of 11% at the end of 7 days of cultivation period compared and to C. pyrenoidosa resulted in 7% at the end of 10 days, respectively. Whereas protein content of Chlorella sp. was found to be higher at 44% compared to 29% of Euglena sp. A significant increase was also observed in carbohydrates in C. pyrenoidosa at the end of 10 days. Whilst NH4+‐N was completely removed by immobilized Chlorella sp., it was reduced by 96% compared to Euglena sp. Further, 98% PO43−‐P removal was achieved with immobilized cultures of both species in two modes of operation. Biological oxygen demand and chemical oxygen demand were observed in the range of significant decrease (~80%–96%) by this approach. © 2014 Curtin University of Technology and John Wiley & Sons, Ltd.